Pengaruh Latihan Slalom Dribble Terhadap Peningkatan Keterampilan Dribbling Sepakbola Pemain SSB Sendang FC U-12 - Mahya, Hamim; Arifai, Arifai (Jurnal Porkes, 2025)
This study aims to determine the effect of the slalom dribble training method on improving the dribbling ability of U-12 SSB Sendang FC players.  The method used for this research is an experiment with a one group pretest-posttest design. The population involved in this study amounted to 55 people, and the sample used was 20 people, using purposive sampling technique. The instrument used in this study was a soccer skill test (dribbling test). The pretest results showed an average dribbling time of 22.23 seconds, while the posttest results increased with an average time of 20.50 seconds. As shown by the normality and homogeneity tests, the data is normally distributed and homogeneous. Therefore, hypothesis testing can be carried out. The t-test results for paired samples showed a Sig. (2-tailed) of 0.000 (< 0.05), indicating that slalom dribble training has a significant effect on the players' dribbling ability. This increase reflects the effectiveness of the method in training players' speed, agility, and coordination. So it is concluded that slalom dribble training can be recommended as a technical coaching method in the development of early childhood soccer dribbling skills.